Intensive Student Learning Strategies in Improving Academic Competence at Alamien Prenduan University - Martang, Martang; Uswatun Hasanah (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to describe the learning strategies of intensive female students in improving academic competence at Al-Amien Prenduan University. Intensive students face complex academic challenges due to their busy dormitory and lecture schedules, necessitating effective and adaptive learning strategies. This study employed a qualitative, phenomenological approach. Data were collected through observation, semi-structured interviews, and documentation, with informants selected using purposive sampling. Data analysis employed the interactive model of Miles, Huberman, and Saldana, while data validity was tested through diligent observation and triangulation of sources and techniques. The results indicate that the learning strategies employed by intensive female students include systematic study time management and understanding the material before memorizing it. Both strategies have proven effective in improving comprehension, learning consistency, and maintaining academic achievement despite time constraints. The success of learning strategies is supported by the quality of human resources, a conducive Islamic boarding school environment, and adequate learning facilities. While the main inhibiting factors are the conflict between academic and boarding school assignments, as well as a busy schedule. This study concludes that improving the academic competence of intensive female students is the result of implementing effective learning strategies and managing the dynamics of the Islamic boarding school environment.